FLAIR vascular hyperintensity is associated with functional outcome in patients with ischemic stroke receiving endovascular treatment: a meta-analysis - Wang, Chunyan; Wang, Chuanliu; Ni, Yongjun (Frontiers in Neurology, 2024)
BackgroundFluid-attenuated inversion recovery (FLAIR) vascular hyperintensity (FVH) might be useful for predicting and functional outcome in ischemic stroke patients after endovascular thrombectomy (EVT), but its clinical benefit remains controversial. Thus, this study aimed to evaluate the association of FVH on prognosis in ischemic stroke patients who received EVT.MethodsPubMed, Embase, Cochrane Library, Web of Science, and Wanfang databases were searched for potentially eligible studies published up to March 2024. Pooled standard mean difference (SMD), risk ratios (RR) with 95% confidence intervals (CI) were employed to assess the association of FVH on prognosis in ischemic stroke patients who received EVT. All statistical analyses were conducted using STATA 12.0 software.ResultsA total of 10 studies were included in our study. The results indicated that higher FVH score were associated with better prognosis (SMD: 0.80, 95% CI 0.63–0.97). Moreover, the presence of FVH was significant associated with better functional outcome in ischemic stroke patients who received EVT (RR: 0.68, 95% CI, 0.58–0.79).ConclusionThe current meta-analysis suggests that FVH is related the prognosis of ischemic stroke patients after EVT.